Melioidosis with Septic Shock and Disseminated Infection in a Neutropenic Patient Receiving Chemotherapy - Sitthi Sukauichai; Chantana Pattarowas (Case Reports in Infectious Diseases)
Melioidosis is a bacterial infection, caused by Gram-negative bacillus, Burkholderia pseudomallei, widespread in Southeast Asia and the northern part of Australia, resulting in a high mortality rate in severe infection. However, it has rarely been reported in patients with chemotherapy-induced neutropenia. The authors described a case of melioidosis in a neutropenic patient presenting with septic shock after receiving chemotherapy. Blood and urine cultures were positive for Burkholderia pseudomallei, and CT scan showed multiple pulmonary nodules and hepatosplenic abscesses. The patient was successfully treated with antibiotics for the infection and with combined modalities for a malignancy.